Working in the comfort zone: Understanding coworking spaces as post-digital, post-work and post-tourist territory - Karin Fast; André Jansson (Digital Geography and Society, 2024)
Coworking spaces are contradictory places. Typically, they are constructed as connected, domestic-like places for hard work and as recreational, aestheticized destinations for individuals in search of work-life balance and opportunities for partial disconnection. This article contributes an immanent critique of coworking spaces through the overarching notion of “coworking space territoriality”. Our point of departure is the concept of post-digital territoriality, which captures how individuals and organizations in various ways try to counter the downsides of escalating digitalization and reclaim a sense of bounded place. To further elaborate the subversive potentials of coworking spaces, however, the “post-digital” is brought into dialogue with “post-work” and “post-tourist”; two other “post-” concepts that contain ideas and practices that characterize the contradictory nature of coworking spaces. At the intersection of all three facets of territoriality, we argue, the coworking space emerges as a spatially and socially bounded comfort zone. The suggested approach informs the ongoing conversation about the ambiguous role of coworking spaces in broader transformations of society, especially in terms of social inclusion and exclusion. The theoretical arguments are anchored in a substantial literature review as well as in first-hand empirical data from a “hot-desking ethnography” covering ten different coworking spaces in Oslo, Denver, and Palma de Mallorca.